Upaya Pengintegrasian Living Values Education (LVE) dalam Proses Pembelajaran IPA Siswa Kelas IV di MI Tunas Cendekia Cirebon - Suci Muzfirah; Muqowim (Institut Agama Islam Tribakti Kediri, 2021)
One of the problems in every learning process is the lack of life values for students, especially in science learning. The values of life or living values education are very important to be given to students so that the school can produce graduates who are not only superior in academia and cognitive, but in rustakter education and living values education (LVE). In this context, it is very important to review efforts to integrate living values education in the learning process of science grade IV at MI Tunas Cendekia Cirebon. In order to get the results of the research, the method carried out by researchers is a descriptive qualitative method. The resulting data source is the result of observation, interview, and documentation analysis. The entire data is processed and processed to be presented as a result of the research. The results showed that efforts to integrate living values education (LVE) in the learning process of science students in grade IV at MI Tunas Cendekia Cirebon are students able to understand the values of life and will affect the development of student character. Integration of Islamic education through living values education can also be done so that students can learn Islamic values in the process of science learning through living values education. [Salah satu permasalahan pada setiap proses pembelajaran adalah kurangnya pemberian nilai-nilai kehidupan bagi siswa, khususnya pada pembelajaran IPA. Nilai-nilai kehidupan atau living values education sangat penting untuk diberikan kepada siswa agar sekolah dapat menghasilkan lulusan yang tidak hanya unggul di bidang akademisi dan kognitif, tetapi dalam pendidikan karatakter dan living values education (LVE). Dalam konteks inilah, sangat penting untuk mengkaji upaya pengintegrasian living values education dalam proses pembelajaran IPA kelas IV di MI Tunas Cendekia Cirebon. Agar mendapatkan hasil penelitian, metode yang dilakukan oleh peneliti adalah metode kualitatif deskriptif. Sumber data yang dihasilkan adalah hasil pengamatan, wawancara, dan analisis dokumentasi. Keseluruhan data diolah dan diredukasi untuk dipaparkan sebagai hasil dari penelitian. Hasil penelitian menunjukan, upaya pengintegrasian living values education (LVE) dalam proses pembelajaran IPA siswa kelas IV di MI Tunas Cendekia Cirebon adalah siswa mampu memahami nilai-nilai kehidupan dan akan berpengaruh pada perkembangan karakter siswa. Pengintegrasian pendidikan keislaman melalui living values education juga dapat dilakukan sehingga siswa dapat mempelajari nilai-nilai keislaman dalam proses pembelajaran IPA melalui living values education]